2012
DOI: 10.1002/masy.201251001
|View full text |Cite
|
Sign up to set email alerts
|

New Trends for Utilization of Rubber Wastes

Abstract: The scrape rubber is difficult to recycle, since it is not thermoplastic material. Consequently, it must be converted into a powder. The scrape rubber powder can be reused via different ways: a-Reclamation The reclamation process was studied. This process converts the rubber powder into elastic-plastic materials. The obtained reclaims were introduced into NR formulations. The obtained data reveal that, 10-30% reclaimed rubber can replace virgin NR without scarifying the basic properties of the rubber vulcaniza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…The antagonism is not proportional and the positive effect in the pristine state is more important (see the associated coefficients in equations 3 and 4 in Table 4). In addition to the stiffening effect of GTR in its basal mechanical properties, it has also been demonstrated that the curing behaviour is affected by the presence of GTR, through the migration of sulphur or accelerators between the vulcanised GTR and the matrix [36].…”
Section: Main Effect and Interaction Plot For Tensile Strength In The...mentioning
confidence: 99%
“…The antagonism is not proportional and the positive effect in the pristine state is more important (see the associated coefficients in equations 3 and 4 in Table 4). In addition to the stiffening effect of GTR in its basal mechanical properties, it has also been demonstrated that the curing behaviour is affected by the presence of GTR, through the migration of sulphur or accelerators between the vulcanised GTR and the matrix [36].…”
Section: Main Effect and Interaction Plot For Tensile Strength In The...mentioning
confidence: 99%
“…Therefore, rubber products such as rubber tires and sealants, which are made from crosslinked rubber, cannot be recycled by conventional methods. One way to make use of them is that they need to be ground and mixed with other thermoplastics to be used as fillers [9,10]. However, there is one material that is elastic, similar to rubber, while it can be reprocessed similar to thermoplastics, which is called thermoplastic vulcanizate [11,12].…”
Section: Introductionmentioning
confidence: 99%